KAJIAN STRATEGI PENYUSUNAN ANGGARAN BISNIS SYARIAH TERHADAP PERTUMBUHAN PERUSAHAAN - Natsir, Imron (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research examines strategies for preparing sharia business budgets in encouraging company growth. The method taken is a literature study, examining various sources to understand the relationship between budget preparation and company development. From this analysis, it was found that a budget strategy that prioritizes sharia principles, while also focusing on operational efficiency and innovation, has a significant influence on company performance. This success is characterized by stable and sustainable growth, showing that sharia values and modern business principles can work well in synergy. This study confirms that a strong commitment to sharia rules, while not ignoring the importance of innovation, is the main key to success in the contemporary business world. The results provide concrete evidence that an effective sharia budgeting strategy is able to advance the company in the long term.